Lateral variations in foreland flexure of a rifted continental margin: The Aquitaine basin (SW France) - Angrand, P; Ford, M; Watts, A (American Geophysical Union, 2018)
Rift inheritance can play a key role in foreland basin geometry and behavior. If the foreland basin initiates soon after rifting, thermal cooling can also contribute significantly to subsidence. We investigate the effects of crustal inheritance (Aptian-Cenomanian rifting) on the evolution of the Campanian to middle Miocene flexural Aquitaine foreland basin, northern Pyrenees, France. Surface and subsurface data define rifted crustal geometry and postrift thermal subsidence. Analysis of Bouguer gravity anomalies coupled with flexural modeling constrains the lateral variations of elastic thickness, plate flexure, and controlling loads. The Aquitaine foreland is divided along-strike into three sectors. The relative role of surface and subsurface (i.e., buried) loading varies along-strike, and the elastic thickness values decrease from the northeast (25 km) to the southwest (7 km) where the plate is the most stretched. The eastern foreland crust was not rifted and underwent a simple flexural subsidence in response to orogenesis. The central sector was affected by crustal stretching. Here the basin is modeled by combining topographic and buried loads, with postrift thermal subsidence. In the western sector, the foreland basin was created mainly by postrift thermal subsidence. The eastern and central sectors are separated by the Eastern Crustal Lineament, which is one of a series of inherited transverse faults that segment the orogen.